Combined classifier based on feature space partitioning - Woźniak, Michał; Krawczyk, Bartosz (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents a significant modification to the AdaSS (Adaptive Splitting and Selection) algorithm, which was developed several years ago. The method is based on the simultaneous partitioning of the feature space and an assignment of a compound classifier to each of the subsets.
Keywords: pattern recognition; combined classifier; multiple classifier system; clustering and selection algorithm; evolutionary algorithms